Workplace innovation and technological change - Beblavy, Miroslav; Maselli, Ilaria; Martellucci, Elisa (Brussels, 2012)
"This paper explores the extent to which that elusive phenomenon called “workplace innovation” has pervaded workplaces in Europe and whether it could be one of the answers to Europe’s long-term social and economic challenges that stem from an ageing workforce and the need for more flexibility to stay competitive. Basic data drawn from European Working Conditions Survey conducted every five years by the Dublin-based European Foundation for the Improvement of Living and Working Conditions are supplemented by a series of case studies to look at the problems encountered in introducing workplace innovation and possible solutions. One set of case studies examines the following organisations: SGI/GI (Slovak Governance Institute (Slovakia), as representative of the world of small- and medium-sized enterprises; Oticon (Denmark) as representative of manufacturing companies; the Open University (UK), as representative of educational organizations; and FPS Social Security (Belgium) representing the public sector. Two final case studies focus on the country-level, one looking at of how a specific innovation can become fully mainstreamed (in the Netherlands and the ‘part-time economy’) and the other (Finland and TEKES) looking at how a government programme can help disseminate workplace innovation. These six case studies, together with the statistical analysis, constitute the main empirical value added of the report."